2SPD-040 Is pneumatic tube delivery safe for medicines?. (March 2019) - Wunder, C; Länger, G
Abstract : Background: Sending drugs by pneumatic tube system is an efficient alternative in large hospital areas, especially in emergency cases. But modern systems are high-speed constructions and this creates high gravitational forces on the products. Purpose: The purpose of our study was to examine the influence on the stability of packaging, various pharmaceutical preparations and active ingredients. Material and methods: G-forces created in the pneumatic tube system were evaluated by accelerometer. Furthermore, variations of temperature were monitored during the transportation process. Different pharmaceutical forms (e.g. powder, ointments, emulsions), packaging materials and loadings were tested under worst-case conditions (mostly remote ward, more than three delivery processes per product). Afterwards the integrity and stability of the products were analysed following pre-defined procedures. In addition, literature research was performed to identify unstable molecules that may not be sent under these conditions. Results: Our literature research showed that especially protein-based medicines (e.g. antibodies) are characterised by low stability when confronted with physical stress. Therefore, these products were excluded from this study as well as cytotoxic drugs, dangerous goods and compressed-gas containers. During the conducted 60 rides, temperature stayed within the limit of 15°C–25°C. Maximum g-force measured was 16 g. We detected the following issues: Powder or ointments leak from plastic containers; Multi–phase formulations tend to separate; Powder in ampules are compressed irreversibly into the head of the ampule; and Emulsions are destroyed by increasing viscosity. Conclusion: Our results prove that protection of primary packaging is not enough. The influence of strong g-forces on the stability of pharmaceutical preparations and molecules has to be observed. Hospital pharmacists have to bring their knowledge of physical drug stability. However, the analytical methods in hospital pharmacies are limited and the stability analysis of such complex molecules such as antibodies cannot be performed in our setting. We consider SOPs, created by hospital pharmacists, which define the appropriate use necessary for a safe pneumatic tube delivery to prevent quality defects and patient harm. References and/or acknowledgements: https://ejhp.bmj.com/content/23/6/343 https://link.springer.com/article/10.1007%2Fs12272–014–0521–3 No conflict of interest.